Effect of lactobacillus strains on phenolic profile, color attributes and antioxidant activities of lactic-acid-fermented mulberry juice. (1st June 2018) - Kwaw, Emmanuel; Ma, Yongkun; Tchabo, William; Apaliya, Maurice Tibiru; Wu, Meng; Sackey, Augustina Sackle; Xiao, Lulu; Tahir, Haroon Elrasheid
Highlights: Effects of lactic acid fermentation on mulberry bioactive compounds and bioactivities were studied. Lactic acid fermentation affected positively the phenolic profile of the juice. Antioxidant activities of mulberry juice were improved after the fermentation. Fermentation using L. plantarum exhibited the highest desirability. Abstract: This study was conducted to investigate the effect of lactic acid bacteria (LAB) strains on color properties, phenolic profile and antioxidant activities of mulberry juice. Mulberry juice was separately fermented at 37 °C for 36 h using Lactobacillus plantarum, Lactobacillus acidophilus and Lactobacillus paracasei . The results showed that lactic acid fermentation impacted on the color of the juice. Moreover, the study demonstrated that LABs impacted on the phenolic profile of the juice. Syringic acid, cyanidin-3-O-rutinoside and quercetin were the predominant phenolic acid, anthocyanin and flavonol respectively in the lactic-acid-fermented mulberry juice. The degree of radical scavenging activity was species-specific with the L. plantarum fermented juice having the highest radical scavenging activities. The correlation analysis demonstrated that flavonols and anthocyanins were mostly responsible for the increased in 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) scavenging activity while phenolic acids and flavonols were responsible for 2, 2-diphenyl-1-picrylhydrazyl scavenging activity and reducing power capacity of the fermented juice.